Fabrication of large‐sized silica monolith exceeding 1000 mL with high structural homogeneity. Issue 12 (18th May 2013) - Miyamoto, Riichi; Ando, Yukiko; Kurusu, Chie; Bai, Hong‐zhi; Nakanishi, Kazuki; Ippommatsu, Masamichi
<x xml:space="preserve">Abstract</x> Reproducible fabrication of the hierarchically porous monolithic silica in a large volume exceeding 1000 mL has been established. By the hydrothermal enlargement of the fully accessible small pores to exceed 50 nm in diameter, the capillary force emerged on solvent evaporation was dramatically reduced, which allowed the preparation of crack‐free monoliths with evaporative solvent removal under an ambient pressure. The local temperature inhomogeneity within a reaction vessel in a large volume was precisely controlled to cancel the heat evolved by the hydrolysis reaction of tetramethoxysilane and that consumed to melt ice cubes dispersed in the solution, resulting in large monolithic silica pieces with improved structural homogeneity. Homogeneity of the pore structure was confirmed, both on macro‐ and mesoscales, using SEM, mercury intrusion, and nitrogen adsorption/desorption measurements. Furthermore, the deviations in chromatographic performance were examined by evaluating multiple smaller monolithic columns prepared from the monolithic silica pieces cut from different parts of a large monolith. All the daughter columns thus prepared exhibited comparable performances to each other to prove the overall homogeneity of the mother monolith. Preliminary results on high‐speed separation of peptides and proteins by the octadecylsilylated silica monolith of the above production have also been demonstrated.